THE DISCOVERY OF SARCODARIANS AND THE WORKS OF F DUJARDIN - BELTRAN, ENRIQUE (INSTITUTO MEXICANO DE RECURSOS NATURALES RENOVABLES, 1933)
Use of nivaquin in 37 cases of giardiasis (Giardia lamblia) resulted in permanent elimination of infection in 32 (865%) In the other 5 the organisms were not wholly eliminated, but which of 3 possible causes was involved in their recurrence could not be
REV SOC MEX HIST NAT
Keywords: DISCOVERY, SARCODARIANS, WORKS, F DUJARDIN; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); PROTOZOOLOGIA